TRAINER PEMBANGKIT LISTRIK TENAGA SURYA - Subandi - (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2017)
Energy consumption in Indonesia has increased, specifically in the industrial and the household sector. Based on EDSM’s 2013 report, industrial sector is the largest of energy consumption 33%, the household sector 27% and the transport sector 27%. While the commercial sector for raw materials 10%. Supporting the development of renewable energy, specifically for solar energy conversion into electricity, it takes a learning tool as an observation of this energy use. For the society, to escalate practical knowledge of solar cells and panels trainer is required to test and experiment as a medium of learning in the academic theoretically to explore the potential of renewable energy. With observations and tests performed on the Solar Electricity Trainer as a medium of learning, capable to improve knowledge in theoretically and experimentally. Based on pretest with the participants called praktikan, with an increase of 47.9%. The result of solar cell test show that accuracy percentage average is 98.37% and the efficiency of the solar charger control reaches 84% ​​for charging the battery by solar cell module.